Absence of clinical or physiological changes during short-term cerebellar stimulation in a patient with Lafora body disease. Issue 4 (April 1981) - Wright, G D; McLellan, D L
Abstract : A 17-year-old girl with Lafora body disease received short-term stimulation but her epilepsy failed to improve and no changes were detected in her EEG. Neither visual nor somatosensory evoked potentials were changed by short bursts of cerebellar stimulation.